The Importance of Gender-Based Standard Operating Procedures for Disaster Management in East Java - Zainal Abidin Achmad; Praja Firdaus Nuryananda; Jelita Arinal Haq; Gideon Setyo Budiwitjaksono; Zalfa Nurrahmah Agustina (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
Disaster management addresses gender inequality by mitigating adverseeffects on women. Involving women in disaster risk reduction is crucial, buttheir participation is often insufficient, leading to inadequate attention totheir specific needs. In Indonesia, where women make up over half thepopulation, their involvement in disaster management is essential. Thisstudy explores women’s disaster risk mitigation strategies and emphasizesgender-responsive disaster management approaches. Following the 2021Mount Semeru eruption, research in East Java revealed gender-sensitivedisaster management deficiencies. Traditional methods often fail to supportwomen and children who are particularly vulnerable. The study highlightsthe importance of education, training, and gender-sensitive disastermanagement policies. Using a phenomenological approach, the studyconducted direct observations, in-depth interviews, and focus groups. Itidentified 24 significant obstacles in gender-based disaster management,such as inadequate casualty statistics and the lack of gender-specificinfrastructure in refugee camps. The research underscores the need forgender-specific standard operating procedures (SOPs) to safeguard womenand children's well-being during and after disasters. Enhancing educationand capacity-building in vulnerable villages is also crucial for effectivedisaster mitigation. To improve disaster resilience, it is essential to integratewomen into the disaster management framework, acknowledging theirspecific needs and harnessing their capabilities.